Plan de exportación de mermelada de uvilla al mercado de Alemania - Sánchez Saavedra, Priscilla Josefina (2020)
Germany is a country known for its preference in exotic fruits that also favors its derivatives by the ease of conservation and consumption, responding to its accelerated lifestyle. The purpose of the project is to develop a plan for exporting physalis peruviana marmalade to said market, strengthening the diversification of the national offer with value-added products, placing the ASSOCIATION OF AGRICULTURAL PRODUCERS ASSOCIATION of the PATAÍN ASOPRUV canton of the Salcedo province of Cotopaxi canton as the main beneficiary…….